Management of fracture-related infection in low resource settings: how applicable are the current consensus guidelines?. Issue 6 (31st May 2022) - Tissingh, Elizabeth K; Marais, Leonard; Loro, Antonio; Bose, Deepa; Paner, Nilo T; Ferguson, Jamie; Morgensten, Mario; McNally, Martin
Abstract : The global burden of fracture-related infection (FRI) is likely to be found in countries with limited healthcare resources and strategies are needed to ensure the best available practice is context appropriate. This study has two main aims: (i) to assess the applicability of recently published expert guidance from the FRI consensus groups on the diagnosis and management of FRI to low- and middle-income countries (LMICs); (ii) to summarise the available evidence on FRI, with consideration for strategies applicable to low resource settings. Data related to the International Consensus Meeting Orthopaedic Trauma Work Group and the International Fracture Related Infection Consensus Group FRI guidelines were collected including panel membership, country of origin, language of publication, open access status and impact factor of the journal of publication. The recommendations and guidelines were then summarised with specific consideration for relevance and applicability to LMICs. Barriers to implementation were explored within a group of LMIC residents and experienced workers. The authorship, evidence base and reach of the FRI consensus guidelines lack representation from low resource settings. The majority of authors (78.5–100%) are based in high-income countries and there are no low-income country collaborators listed in any of the papers. All papers are in English. The FRI consensus guidelines give a clear set of principles for the optimum management of FRI. Many of these – including the approach to diagnosis, multidisciplinary team working and some elements of surgical management – are achievable in low resource settings. Current evidence suggests that it is important that a core set of principles is prioritised but robust evidence for this is lacking. There are major organisational and infrastructure obstacles in LMICs that will make any standardisation of FRI diagnosis or management challenging. The detail of how FRI consensus principles should be applied in low resource settings requires further work. The important work presented in the current FRI consensus guidelines is relevant to low resource settings. However, leadership, collaboration, creativity and innovation will be needed to implement these strategies for communities who need it the most.